Estimation of potential risk of ACL rupture in female soccer players and effectiveness of a prevention training program - Jöllenbeck, T.; Grebe, B.; Neuhaus, D. (ISBS - Conference Proceedings Archive (Konstanz), 2009)
The purpose of this study was to make an estimation of the potential risk of ACL rupture in female soccer players by means of video based analysis and controlled by biomechanical testing as well as to relate to effects by carrying out an 8 week specific training program. Results show that video based screening seems to be suitable in order to achieve a good estimation of the risk for ACL injuries without large expenditure. The performed ACL prevention training program shows a slight reduction of the potential risk of ACL rupture.